Assessment of Waste Management Awareness and Practices among Par-ents: A Sequential Explanatory Study - Sambat, Lanah Maria D.; Bulaun, Cassandra M.; Soliman, Rachel Ann D.; Muñoz, Ezequel R.; Hu, Anabel S.; Deang, Mark Anthony C.; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study explores parents’ awareness and practices on solid waste management. It shows the significance of solid waste segregation for parental involvement and how it influences parents' attitudes and behaviors in a barangay in Magalang, Pampanga. The parents benefit from this study by learning more about the practices and appropriate segregation within their community. In this study, which involved 100 parents, a mixed-method sequential explanatory technique was employed. The results indicate that parents are not aware of the relevant laws about solid waste management and the sources of information about it. In terms of practices, parents are productive at disposing of, reducing, and recycling solid waste, but they don't reuse and segregate the solid waste that much. Overall, the results highlight how crucial proper waste sorting, awareness-building, community involvement, resourcefulness, and sustainability are to improve waste management. Although there are challenges, such as a lack of awareness and inconsistent efforts, recycling and waste removal are mentioned as sources of satisfaction. Parents also emphasize the need for proper segregation, solid waste management regulations, and providing incentives to promote sustainable behaviors in the barangay.